2018
DOI: 10.1007/s00268-018-4530-0
|View full text |Cite
|
Sign up to set email alerts
|

Defining Early Recurrence of Hilar Cholangiocarcinoma After Curative‐intent Surgery: A Multi‐institutional Study from the US Extrahepatic Biliary Malignancy Consortium

Abstract: Early recurrence of HCCA after curative resection was common (~35.6%). Early recurrence was strongly associated with aggressive tumor characteristics, increased risk of distant metastatic recurrence and a worse long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 61 publications
4
42
0
Order By: Relevance
“…However, median overall survival in our study is in line with published (and partly older) retrospective analyses [18,8,21,23], underscoring the need for new treatment strategies, since no improvement of survival could be detected over the past decades. R0 resection rates for patients amenable to surgery were slightly higher in our study than reported in the literature [7][8][9][10], which might be due to selection bias and/or mandatory multidisciplinary treatment decisions in our center.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, median overall survival in our study is in line with published (and partly older) retrospective analyses [18,8,21,23], underscoring the need for new treatment strategies, since no improvement of survival could be detected over the past decades. R0 resection rates for patients amenable to surgery were slightly higher in our study than reported in the literature [7][8][9][10], which might be due to selection bias and/or mandatory multidisciplinary treatment decisions in our center.…”
Section: Discussionsupporting
confidence: 89%
“…Survival and prognosis in patients with CCA in a curative and palliative setting have not profoundly improved in the past years [1,18]. Data on survival rates, prognostic-and risk factors mainly come from retrospective studies similar to the one presented here [7][8][9][19][20][21]. Of note is that a large number of retrospective analyses also included patients being treated back to the early 1990s [7][8][9] or even earlier [19,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 21 patients died within 90 days after surgery and were excluded from the analysis to reduce the impact of postoperative complications when assessing the recurrence rates and calculating the optimal cutoff point for early recurrence. 19,20 The postoperative complication rate after surgery was 44.8% (n = 184), which included 117 patients with CD II or higher complications. Major complications (CD II-III) consisted of bile leakage (n = 28), peritoneal cavity infection (n = 14), lung infection (n = 18), sepsis (n = 4), hemorrhage (n = 13), hepatic failure (n = 18), renal failure (n = 2), stress ulcer (n = 7), and others (n = 13).…”
Section: Characteristics Of the Study Populationmentioning
confidence: 99%
“…Early recurrence after curative surgery has been associated with poor prognosis in hepatic carcinoma. 19,33,34 Zhang et al 19 defined radiologically diagnosed recurrence within 2.5 years after curative surgery as early recurrence in HC patients. The difficulty to achieve negative resection margin for type IV HC renders relatively worse prognosis.…”
Section: Univariate and Multivariate Analysis Of Clinicopathologic Inmentioning
confidence: 99%
See 1 more Smart Citation